2006
DOI: 10.1182/blood-2005-06-2345
|View full text |Cite
|
Sign up to set email alerts
|

CD4+/CD8+ macrophages infiltrating at inflammatory sites: a population of monocytes/macrophages with a cytotoxic phenotype

Abstract: We found a population of nonlymphoid cells expressing both CD4 and CD8 in peripheral blood mononuclear cells (PBMCs) of human T-cell leukemia virus type-I pX transgenic rats with autoimmune diseases. These cells, which showed a monocytic phenotype, were also found in wild-type rats, and their number increased by adjuvant-assisted immunization. GM-CSF increased the number of these double-positive (DP) monocytes in PBMCs. Consistent with the idea that DP monocytes differentiate into DP macrophages at sites of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 42 publications
1
45
0
2
Order By: Relevance
“…It was recently reported that bone marrow DC (BMDC) cytotoxic activity requires a direct contact with target tumor cells and depends on NO production (14). NKR-P2/NKG2D is a disulfide-linked type II C-type lectin-like receptor expressed also on NK cells, CD4 ϩ , CD8 ϩ ␣␤, ␥␦ ϩ T cells (15), rat CD4 ϩ /CD8 ϩ monocytes and macrophages (16), mouse IFN-producing killer DCs (17,18), and human myeloblastic KG1a cells (19).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…It was recently reported that bone marrow DC (BMDC) cytotoxic activity requires a direct contact with target tumor cells and depends on NO production (14). NKR-P2/NKG2D is a disulfide-linked type II C-type lectin-like receptor expressed also on NK cells, CD4 ϩ , CD8 ϩ ␣␤, ␥␦ ϩ T cells (15), rat CD4 ϩ /CD8 ϩ monocytes and macrophages (16), mouse IFN-producing killer DCs (17,18), and human myeloblastic KG1a cells (19).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…In our previous study, we demonstrated that CD4 ϩ CD8 ϩ macrophages were able to kill the malignant thymoma cell line MT in vitro (1). Killing was dose dependent and reached the peak when the E:T ratio was 30.…”
Section: Cd4mentioning
confidence: 99%
“…In our previous study, we identified a novel subpopulation of monocyte/macrophage lineage cells expressing both CD4 and CD8 (1). When rats were immunized with adjuvants containing killed tuberculosis germs, CD4 ϩ CD8 ϩ monocytes and macrophages were expanded in peripheral blood and spleen, respectively.…”
Section: Onocyte/macrophage Lineage Cells and Dendritic Cells (Dcs)mentioning
confidence: 99%
“…Samples were treated with 1 unit/lL of DNase I for 15 min at room temperature to avoid contamination of DNA. The purified RNAs were reverse-transcribed by Superscript III reverse transcriptase (Invitrogen), using oligo-dT primers as previously described (4 0 (antisense). PCR amplification was performed for 35 cycles of 1 min at 948C, 1 min at 568C, and 1 min at 728C.…”
Section: Flow Cytometry (Fcm)mentioning
confidence: 99%
“…We previously reported that CD8ab heterodimers were expressed on a novel subpopulation of macrophage lineage cells in rat peripheral blood (4). These cells are precursors of CD8ab 1 macrophages infiltrating into tissues with inflammation.…”
mentioning
confidence: 99%